Thinking critically about critical thinking: validating the Russian HEIghten® critical thinking assessment. Issue 9 (1st September 2020) - Shaw, Amy; Liu, Ou Lydia; Gu, Lin; Kardonova, Elena; Chirikov, Igor; Li, Guirong; Hu, Shangfeng; Yu, Ningning; Ma, Liping; Guo, Fei; Su, Qi; Shi, Jinghuan; et al.
ABSTRACT: Critical thinking has been identified as a crucial general skill contributing to academic and career success in the twenty-first century. With the increasing demands of the modern workplace and a global trend of accountability in higher education, educators and employers pay great attention to the development of students' critical thinking skills throughout their training. Therefore, there is an urgent need worldwide for an updated and comprehensive assessment tool of college-level critical thinking. This paper reports on the preliminary validation for the Russian version of the HEIghten ® Critical Thinking assessment developed by Educational Testing Service (ETS). Based on a large Russian college student sample ( N = 1060), we evaluated the psychometric quality of the items, individual and institution-level reliability, external validity, and student perceptions. Overall, the results suggested good psychometric quality, except that a few items showed low discriminating power and should be further examined with a second wave of data collection. IRT analyses revealed testlet effects and supported the essentially unidimensional structure of the measure. Appropriate correlations with external criteria provided support for the measure's convergent validity. Implications of the preliminary validation study results and the future research agenda, especially the need to collect longitudinal data, are discussed.